Validacija prijevoda upitnika SIPP-118 i kratke verzije upitnika PID-5 - Gazdek, Tamara; Klasić, Katarina; Žulj, Andrea; Ručević, Silvija; Krupić, Dino (2020)
Brojna istraživanja upućuju na važnost osobina ličnosti u predikciji različitih oblika rizičnog ponašanja kod adolescenata. U proteklih je nekoliko godina razvijen niz upitnika ličnosti koji su se pokazali uspješnim u predikciji rizičnog ponašanja. Većina tih upitnika nije prevedna na hrvatskom jeziku. Cilj je ovog istraživanja prikazati hrvatske prijevode Upitnika simptoma poremećaja ličnosti (SIPP-118) te kratke verzije Inventara ličnosti za DSM-5 (PID-5). Za procjenu konvergentne valjanosti upitnika PID-5 korištena je Dimenzionalna procjena osobina ličnosti (DiPOL), dok se Samoiskaz rizičnog i delinkventnog ponašanja mladih (SRDP) koristio za ispitivanje prediktivne valjanosti upitnika PID-5 i SIPP-118. Istraživanje je provedeno na 497 učenika gimnazije i strukovnih škola iz Osijeka, Belog Manastira, Đakova i Donjeg Miholjca. Rezultati konfirmatorne faktorske strukture upitnika SIPP-118 nisu potvrdili očekivanu faktorsku strukturu. Petofaktorska struktura upitnika PID-5 pokazala se najboljim modelom, no skale su međusobno suviše povezane što umanjuje divergentnu valjanost upitnika. Rezultati pokazuju kako su osobine ličnosti i indeks funkcioniranja ličnosti umjereno povezani s tendencijom rizičnog ponašanja. Hijerarhijska regresijska analiza pokazala je da se veći udio varijance u rizičnom ponašanju može objasniti upitnikom DiPOL u odnosu na PID-5. S obzirom na rezultate istraživanja savjetujemo oprez pri korištenju prevedenih upitnika.
Vast research indicates the importance of personality traits in predicting different types of risk behaviour in adolescents. In the last couple of years, several personality questionnaires have been successful in predicting risk behaviour in adolescents. The majority of these questionnaires have not been adapted in the Croatian language. The goal of this survey is to show Croatian translation of the Severity Indices of Personality Problems (SIPP-118) and the short version of the Personality Inventory for DSM-5 (PID-5). Dimensional Assessment of Personality Questionnaire (DAPQ) has been used to assess the convergent validity of PID-5 questionnaire, while Self-reported Delinquency and Risk Behaviours Questionnaire (SRDP) has been used for the assessment of the predictive validity of PID-5 and SIPP-118. The survey was conducted on 497 high school and vocational students in Osijek, Beli Manastir, Đakovo and Donji Miholjac. The results of the confirmatory factor structure of SIPP-118 questionnaire did not confirm the anticipated factor structure. Five-factor structure PID-5 has been declared as the best model, but the scales are highly interrelated, which diminishes the divergent validity of the questionnaire. The results show that personality traits and personality functioning scales are moderately related to the tendency to risk and socially unacceptable behaviour. The hierarchical regression analysis has shown that a larger part of the variance in risk behaviour can be explained using DAPQ questionnaire than using PID-5. Considering the results of this survey, caution is advised in using translated questionnaires.
Bibliografija: str. 286-289.
Sažetak ; Summary.
Keywords: Rizično ponašanje -- Adolescenti -- Poremećaji ličnosti -- Upitnik